Investigations of Radiation Characteristics of a circularly polarized conical beam spherical slot array antenna - Phongcharoenpanich, Chuwong; Krairiksh, Monai; Takada, Jun Ichi (My University, 1999)
This paper presents the radiation characteristics of a circularly polarized conical beam spherical slot array antenna for applying to the mobile satellite communication subscriber. The structure of the antenna is easy to fabricate i.e., a ring of perpendicular slot pairs cut on an outer surface of a concentric conducting spherical cavity enclosed by the conducting conical surface with the simple feeding structure, and a linear electric probe excited at the center of the inner surface of the cavity. Radiation fields of a spherical slot array antenna are calculated by superposing the patterns of all the slots. From the numerical results of the radiation pattern, in both elcvational and azimuthal planes, it is obvious that the conical beam is realized. The elevational beam direction is low, which is suitable for installing in the land mobile subscriber unit located far from the equator. The tracking system is not necessary because the azimuthal pattern is omnidirectional. Directivity of the antenna for various spherical radii and angles of slot positions are illustrated as the guidelines for the design. Experimental results are in good agreement with the predictions.
Keywords: Circular polarization; Conical beam; Mobile satellite antenna; Spherical slot array antenna